Chinatown Art Brigade: Resisting gentrification through the power of art, culture and stories. Issue 2 (1st June 2017) - Yu, Betty
The Chinatown Art Brigade is a collective of Asian American artists, media makers and activists with roots in NY Chinatown. Since its founding in 2015 by artists Betty Yu, ManSee Kong and Tomie Arai, The Chinatown Art Brigade has facilitated a series of community led responses to gentrification and displacement, created in partnership with the Chinatown Tenants Union, a programme of CAAAV Organizing Asian Communities. Our work is driven by a deep love for our community and the fundamental belief that fighting against racial and economic inequity must be central to our cultural and art making process.